Awareness, knowledge, and attitude towards body donation among medical and paramedical students - Sarita Behera; Ravindra Kumar Chowdhury; Mamata Sar; Srikanta Kumar Mishra (Wolters Kluwer Medknow Publications, 2023)
Background: Cadavers are the mainstay of learning anatomy by dissection. Due to insufficient awareness of body donation, most of the medical institutions are facing a shortage of cadavers. Health-care professionals should have knowledge about the complete process of body donation, so that they can become motivators of organ and body donation. The present study was conducted to determine and compare the awareness, knowledge, and attitude regarding body donation among medical and paramedical students. Methodology: A cross-sectional and comparative study was conducted among 182 medical and 119 paramedical students through a pretested semistructured questionnaire via a Google form. The Chi-square test was used for the estimation of the P value. Results: 96.7% of medical students and 93.2% of paramedical students had heard about the concept of body donation. 31.8%medical and 49.5% of paramedical students (P < 0.00001) knew that body donation and eye donation can be done simultaneously. The cadavers available are not adequate was felt by 45% of medical and 42.8% of paramedical groups. 90.1% of medical and 86.5% of paramedical students opined for the inclusion of a chapter on body donation. The virtual anatomy table cannot be a substitute for body donation was perceived by 78% of medical and 15.1% of paramedical students (P < 000001). 34.6% of medical students and 56.3% of paramedical students have shown their willingness to donate their whole body and eyes. Conclusion: Although medical and paramedical students have heard about the concept of body donation, their awareness, knowledge, and attitude need to be improved.